Multi-Agent Based Context Aware Multicast Routing in VANET - Devangavi, AD; Gupta, Rajendra (International Journal of Computer Sciences and Engineering, 2025)
Vehicular Ad-hoc Network (VANET) is a variant of Mobile Ad-hoc Network (MANET).The key goal of VANET is to facilitate communications among vehicles and also amongst vehicles and fixed infrastructure. Regardless of the fact that VANET is considered as a sub-class of MANET, it has distinctive features in terms of high mobility of vehicles, fabricating to recurrent topology changes, random node density and boundless network size. Hence most of the clustering algorithms considered for MANET are inappropriate for VANET. Much of the literature recently published focus on clustering in VANETs. However most of them are concentrated on diminishing network overhead value, number of clusters formed and do not consider the vehicles interests (viz. traffic congestion, looking for petrol pumps, free parking space, etc.). To decrease the complexity of transmissions, only context-aware data is required to be communicated to the intended recipients as needless information may cause a performance bottleneck in VANETs. Hence in this paper, we propose a context aware multicast/clustered routing algorithm based on agent technology which addresses above mentioned issues and improves the performance parameters associated with routing in VANET. The performance of the proposed scheme is tested with respect to bandwidth consumption, cluster formation time, multicast grouping time and communication overhead.